0,6(x-6) + 14,2 = 0,8(8-x)
0,6x - 3,6 + 14,2 = 6,4 - 0,8х 1,4x = -4,2
0,6x + 0,8x = 6,4 + 3,6 - 14,2
1,4x = 10 - 14,2
x = -4,2/1,4 = -42/14 = -3
ответ: х=-3
Проверка
0,6(-3-6) + 14,2 = 0,8(8-(-3))
0,6 (-9) + 14,2 = 0,8.11
-5,4 +14,2 = 8,98 8,98 = 8,98
0,6(x-6) + 14,2 = 0,8(8-x)
0,6x - 3,6 + 14,2 = 6,4 - 0,8х 1,4x = -4,2
0,6x + 0,8x = 6,4 + 3,6 - 14,2
1,4x = 10 - 14,2
x = -4,2/1,4 = -42/14 = -3
ответ: х=-3
Проверка
0,6(-3-6) + 14,2 = 0,8(8-(-3))
0,6 (-9) + 14,2 = 0,8.11
-5,4 +14,2 = 8,98 8,98 = 8,98